Voicing curriculum: Exploring embodied entanglements of arts-based inquiry and refrain - Venter, Z.; Müller, M.; Kruger, F. (South African Journal of Higher Education, 2023)
In this article, we share our understanding of a “more than” (Ulmer 2017, 10) critical curriculum inquiry and how this type of inquiry can help us collapse the subject‒object binary by attentively responding to embodied experiences in curriculum studies. Our focus is specifically on the affective dimension of curriculum inquiry as we work with what St. Pierre (2018, 604) refers to as the “history of the present”. We use education memory to tap into the nuanced intra-actions between post-humanism, curriculum studies and how these are extended into the post-schooling context. We understand education memory as the sensory, affective and embodied experiences of education that emerge as we pause in awareness of our present moment of becoming. We draw on Pinar’s currere as folding memory into the present to continuously give voice to multidimensional layers of imagined futures. We draw on the concept of refrain (Deleuze and Guattari 1988, 300), which we understand as complex lived experiences informative in our becoming as educators. In using arts-based methods such as poetry, object inquiry, drawing and drumming, we explore lived experiences to tangibly integrate memory and imagination on pedagogical refrains that shape our becoming. Arts-based methods and materials afford tactile engagement with materiality and attentive responsiveness. Thus, we ask: How might the concept of refrain, as manifest in an arts-based research approach, allow us to give voice to curriculum entanglements as a “more-than-critical” curriculum? Through this question, we pay attention to relational occurrences as refrains, for memory and improvisation becoming integrated to inform curriculum entanglements between humans and the more-than-human.